The Daily Friendship : the official Gay Games Newspaper. - Stichting Gay and Lesbian Games (Amsterdam : Stichting Gay and Lesbian Games, 1998)
Fonds Suzan Daniel (FSD)
Periodiciteit : dagelijks
Redactie : Amstel 1, 1011 PN Amsterdam
Engels
Krant